The Influence of Organizational Politics on Organizational Commitment and Job Satisfaction and Its Influence On Organizational Citizenship Behavior - Akbar Pahlevi; Rio Dhani Laksana (Green Publisher Indonesia, 2022)
The number of individuals who gather in the organization is directly proportional to the number of interests in the organization. The more individuals who prioritize their interests, the more the goals of the organization will be neglected. Increased perceptions of organizational politics can worsen organizational outcomes. However, many studies stated that organizational politics can improve organizational outcomes. This study examines organizational politics and its effect on commitment and job satisfaction and its effect on OCB. This research is a quantitative-research with the number of respondents as many as 40 salespeople in the furniture sector and analyzed using Partial Least Square (PLS). The results of this study indicate that only one hypothesis is rejected.